The effects of morning preconditioning protocols on testosterone, cortisol and afternoon sprint cycling performance. - McDonald, K.; Maulder, P. (Sport and Exercise Science New Zealand Conference, 2018, 2018)
Opportunity exists for athletes to undertake morning exercise protocols in an attempt to potentate afternoon performance. Four track sprint cyclists involved with Cycling NZ`s development programme completed either a morning cycling (Cyc) or weights (W) based protocol (P) prior to an afternoon 500m cycling time trial. Heart rate, testosterone (T) and cortisol levels were measured along with peak power (PP) in the morning and afternoon. The WP produced significantly (P = 0.018) faster times between 250-500m in comparison to CycP. The anticipated circadian decline of T was observed after the CycP but was however mitigated following the WP. While slight decreases in 500m times were experienced during the WP, they are considered within the normal variations experienced between performances by elite athletes. Differences in morning T levels between protocols may be due to athlete`s motivation to complete each protocol. The effect of the WP on the circadian rhythm of T could be linked to a greater recruitment of muscle fibres. The use of a heavy resistance morning exercise protocol is recommended for positively effecting testosterone levels in the afternoon. Possible gender and individual responses from conducting a W over Cyc protocol may exist but requires further investigation.